Restoration of frequency due to variation of load in an autonomous microgrid - Alamgir, Md. (BRAC Univeristy, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Masters of Science in Electrical and Electronic Engineering, 2018.